MATHEMATICAL ANALYSIS OF UNSTEADY MHD BLOOD FLOW THROUGH PARALLEL PLATE CHANNEL WITH HEAT SOURCE - Surseh, M.V.; Sekar, P. (International Journal of Engineering Technologies and Management Research, 2018)
A mathematical model of flimsy blood move through parallel plate channel under the action of a connected steady transverse attractive field is proposed. The model is subjected to warm source. Expository articulations are gotten by picking the hub speed; temperature dispersion and the typical speed of the blood rely upon y and t just to change over the arrangement of fractional differential conditions into an arrangement of normal differential conditions under the conditions characterized in our model. The model has been breaking down to discover the impacts of different parameters, for example, Hart-mann number, warm source parameter and Prandtl number on the hub speed, temperature circulation, and the ordinary speed. The numerical arrangements of pivotal speed, temperature conveyances, and typical speed are demonstrated graphically for better comprehension of the issue. Subsequently, the present numerical model gives a straightforward type of pivotal speed, temperature circulation and typical speed of the bloodstream so it will help not just individuals working in the field of Physiological liquid elements yet in addition to the restorative professionals.